The Effect of PBL-STEAM Video-Assisted PBL-STEAM Using the Kampung Code Pollution Context - Kilana Kilang Rahimmiditya; Insih Wilujeng (Universitas Lambung Mangkurat, 2026)
This study examines the effect of a video-assisted PBL-STEAM model using the Kampung Code pollution context on junior high school students’ problem-solving ability and environmental care attitude. A quasi-experimental nonequivalent pretest–posttest control group design was employed. The sample consisted of two classes selected through cluster random sampling: one experimental class and one control class. Data were collected using a problem-solving test and an environmental care attitude questionnaire. Data analysis included normalized gain (N-Gain) and inferential statistics using an independent samples t-test and Mann–Whitney test. The results indicate that the experimental group achieved higher improvement in problem-solving ability (N-Gain = 0.35, medium) compared to the control group (N-Gain = 0.15, low), with a statistically significant difference (p = 0.001). In contrast, environmental care attitude showed low improvement in both groups (experimental = 0.14; control = 0.11), with no significant difference (p = 0.569). These findings suggest that video-assisted PBL-STEAM using a local environmental context is associated with improved cognitive outcomes, while affective outcomes may require longer and more sustained interventions.